3D Propulsions of Rod‐Shaped Micropropellers. (30th August 2021) - Zhang, Yuan; Tan, Xiangkui; Li, Xiying; Lv, Pengyu; Huang, Tian-Yun; Yang, Jianying; Duan, Huiling
Abstract : Untethered, magnetically driven microrobots have great potential in practical applications such as minimally invasive surgery. Microrods, also known as "nanowires, " are the most commonly used type of structure for microrobots due to the easy fabrication and promising functions. Driven by a uniform rotating magnetic field, microrods can perform a 2D movement with the assistance of a boundary surface, which severely limits the application of microrods in 3D spaces. Herein, an asymmetric structural design is proposed to construct rod‐shaped micropropellers that can achieve a surface‐free 3D propulsion. A theoretical model is formulated based on resistive force theory to investigate the dynamics of micropropellers. It is theoretically demonstrated and experimentally verified that the magnetic micropropeller can realize not only a 3D propulsion, but also multimodal locomotion to adapt to the environment. The work provides guidance for the design and optimization of autonomous micropropellers. Abstract : An asymmetric structural design is proposed to construct rod‐shaped micropropellers that can realize surface‐free 3D propulsions. These 3D micropropellers have an in‐plane rotating "spinning" mode to gain high speed and an out‐of‐plane biconical rotating "precession" mode to pass through narrow channels with a smaller rotation radius, which makes them more flexible and adaptable.